Nilai rasio netrofil limfosit dan rasio trombosit limfosit pada pasien chronic kidney disease sebelum dan setelah hemodialisa - Nelly Nelly; Yuyun Widaningsih; Fitriani Mangarengi (Intisari Sains Medis, 2019)
Background: CKD is a world health problem with an increasing incidence, having a poor prognosis and requiring expensive treatment costs. Cardiovascular disease is the cause of high mortality rates in CKD patients due to inflammation. Neutrophil to lymphocytes ratio (NLR) and platelet to lymphocyte ratios (PLR) are considered as inflammatory markers that are cheap, fast and easily calculated from the routine blood examination. This study aimed to know the value of RNL and RTL in CKD patients before and after HD as the initial marker of inflammation. Method: Eighty-eight patients with CKD were divided into three groups before HD, after the first HD, and after the third HD. The neutrophil-lymphocyte ratio and platelet-lymphocyte ratio are calculated based on the results of routine blood tests. Data distribution was tested with Kolmogorov-Smirnov and analyzed by appropriate data testing.Results: RNL and RTL values in CKD patients after HD increased compared to before HD (p <0.05). There is a weak correlation between RNL values and serum urea levels. However, the RTL value only correlates with urea before hemodialysis.Conclusion: There are differences in RNL and RTL values in CKD patients before HD, after the first HD and third HD. There is a correlation between the RNL value and the state of uremia that is aggravated by HD